PEMBELAJARAN ENGLISH FOR MEETING MELALUI SIMULASI SIDANG ASEAN PADA SISWA SMAN 1 NGAMPRAH KABUPATEN BANDUNG BARAT (ID) - Hastuti, Ika Sri; Ratna Poerwantika , Tine; Azka Fathia, Natasya (Jurnal Abdi Insani, 2025)
English are used to be the main global language in education, diplomacy, and international collaboration. The EF EPI (2024) indicates that nations with high proficiency levels generally possess enhanced global competitiveness. Consequently, proficiency in formal English is crucial for the younger generation to engage effectively in regional and global discussions. To facilitate this, English for Meeting training at SMAN 1 Ngamprah was conducted as a manifestation of experiential, contextually-based learning. Forty-five grade XI students participated in a simulation of an ASEAN meeting, assuming roles such as chairman, co-chairman, secretariat, and country delegates. The training sought to furnish students with formal English language proficiency in a professional setting, while also enhancing their confidence, collaboration, and analytical skills. The activity was conducted in four phases: needs analysis, theoretical instruction, simulation practice, and evaluation. The preliminary research indicated pupils' diminished confidence in employing formal English in official contexts. During this program, students honed their skills in articulating viewpoints, countering arguments, and delivering concluding statements in a diplomatic manner. The theme of ASEAN environmental issues expanded pupils' global perspectives. The evaluation results indicated substantial enhancement in fluency, formal vocabulary utilization, communication organization, and public speaking confidence. Educators and learners assessed the course as pertinent, efficient, and significantly influential in developing 21st-century competencies.